Entrepreneurship Education, Role Models, and Entrepreneurial Intention: Implications for High School Students’ Entrepreneurial Action - Insani, Yogie Dana; F. Danardana Murwani; Triadi Agung Sudarto (International Journal of Business and Quality Research, 2025)
This study examines the role of Entrepreneurship Education (EE) and Entrepreneurial Role Models (ERM) in fostering Entrepreneurial Action (EA) among Indonesian high school students, using Entrepreneurial Intention (EI) as a mediating factor. While national economic growth relies on entrepreneurship, Indonesia's entrepreneurship rate remains low, highlighting a critical gap in high school students' transition from learning to action. Employing a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) on data from 322 public high school (SMA and SMK Negeri) students in Mojokerto, the results show that EE and ERM significantly and positively influence EA both directly and indirectly through EI. Specifically, ERM exhibits a stronger indirect effect on EA (β = 0.268) compared to EE (β = 0.196), confirming that the presence of successful figures is more effective in galvanizing students' intention to act compared to classroom learning. This research validates the Theory of Planned Behavior and the Social Cognitive Career Theory in the context of Indonesian youth, emphasizing that EI serves as a crucial psychological bridge linking external motivators to tangible entrepreneurial behavior. The findings suggest that educational policy should integrate experiential learning with active, diverse role model exposure to cultivate robust entrepreneurial action in future generations